Depositional characteristics of a relay ramp controlled braided deltaic system: A case study in the Eocene Huizhou Sag, Pearl River Mouth Basin, China - Wenfang Tao; Jiawang Ge; Yongchang Lei; Xubiao Li; Xiaomin Zhu (地质科技通报, 2023)
Objective Tectonic transfer zones (or named as relay ramps) can have a profound impact on the drainages catchment, sediment dispersal and reservoirs distribution patterns; they are also important for hydrocarbon transport and accumulation processes. It is a hot object of current research interest to sedimentary geologists as well as petroleum geologists. A few different types of tectonic transfer zones are observed in the Eocene Huizhou Sag, the Pearl River Mouth Basin, South China Sea. The HZ25 area linking the Huizhou 26 and Xijiang 30 Sags is a typical overlapping transfer zone that controls the development of a large set of braided-deltaic system. Methods Based on newly acquired and processed high-quality 3D seismic data, three drilling logs, cores, and thin slices are utilized to discuss the characteristics of the relay ramp-controlled braided deltaic deposits and reservoirs in this paper. Results The results show that the Late Eocene climate was relatively hot and humid, and thus, abundant terrestrial clastic are collected and transported from the Dongsha Uplift source area via the HZ25 relay ramp routing system. Subsequently, a set of thick-bedded braided-delta deposits was deposited in the HZ26 Sag. The braided deltaic sandstones are generally coarse-grained with relatively poor sorting and roundness. It is dominated by mainly lithic sandstone. The particle size probability curve and C-M diagram display typical multiple traction flow characteristics. Large-scale cross bedding, high-angle inclined bedding and extensive scour surfaces in multistory fining-upwards cycles are common in core observations. It is implied that rich and hydrodynamic traction flow regimes are developed. The drainage dispersal pathways are redirected by the internal tectonic belts within the relay ramp, which are characterized by a large-scale but low-gradient (less than 3 degrees) physiographic slope. Strong hydrodynamic forces associated with facilitated deltaic drainage resulted in a high sand ratio of approximately 52% on average. The maximum advancement of the braided deltaic system is approximately 8 km, and its lobe-like geometry is strictly reorganized by the special tectonic-geomorphic pattern of the relay ramp zone. Conclusion The frontal deposits of the braided deltaic system have relatively good sandstone sorting, and thus, the relevant deposits are characterized by a higher porosity than those observed in the braided-delta plain. The good stratigraphic-lithological traps controlled by the relay ramp coupled with the multiple stages of thick-bedded braided-deltaic deposits are most important in this study area, which could be selected as an exploration potential area in the future. Additionally, the braided deltaic deposits in the study area are mainly dominated by low-porosity and low-permeability reservoirs. The reservoir in the frontal area of the braided deltaic deposits could be a priority exploration and evaluation target for petroleum resources due to its low mud content and miscellaneous bases, moderate sorting and good pore connectivity.